Intestinal absorption of food antigens in coeliac disease. Issue 6 (June 1982) - Pitcher-Wilmott, R W; Booth, I; Harries, J; Levinsky, R J
Abstract : Serum concentrations of ovalbumin, beta-lactoglobulin, and antigen-antibody complexes were measured after jejunal administration of milk and raw egg in 6 children with active coeliac disease and in 4 controls. The results did not support the hypothesis of a generalised increase in absorption of antigens from the intestinal lumen in coeliac disease.